2010
DOI: 10.1177/1934578x1000500412
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chromones in Dysophylla stellata by HPLC: Method Development, Validation and Comparison of Different Extraction Methods

Abstract: An HPLC method with reflux as an efficient extraction method has been developed for quantification of chromones in Dysophylla stellata Benth. Separation was achieved on a C 18 column with a mobile phase of 0.5% (v/v) acetic acid in water (A), and ACN (B) under gradient elution at 1 mL/min. Chromones (1 and 2) isolated from D. stellata were used as standards for method development and validation was achieved according to ICH guidelines. Extracts prepared by three different methods [reflux, ultrasonication and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…While the pH levels of the mobile phase decreased from 4.8, the resolution and tailing factor of OML and P7ME were found to be improved. The declining tailing factor of OML and P7ME in an acidic pH mobile phase is similar to the finding of a prior investigation that established the analytical technique for chromones in Dysophylla stellate [18].…”
Section: Development and Optimization Of The Proposed Hplc-dad Methodssupporting
confidence: 84%
“…While the pH levels of the mobile phase decreased from 4.8, the resolution and tailing factor of OML and P7ME were found to be improved. The declining tailing factor of OML and P7ME in an acidic pH mobile phase is similar to the finding of a prior investigation that established the analytical technique for chromones in Dysophylla stellate [18].…”
Section: Development and Optimization Of The Proposed Hplc-dad Methodssupporting
confidence: 84%
“…The amounts of two chromone compounds ie, 5-hydroxy-2-(2-phenylethyl) chromone (1) and 5-hydroxy-2-[2-(2hydroxyphenyl)ethyl]chromone (2) were evaluated using high-performance liquid chromatography (HPLC) technique following the reflux extraction method described previously. 77 Briefly, standard solutions (1 mg/mL of standards) were prepared by diluting stock solutions with acetonitrile (ACN) to make 2, 4, 6, 8, and 10 µg/mL of 1 and 2.5, 5, 10, 15 µg/mL of 2 , and quantification of the chromones in the herb was performed using high-performance liquid chromatography (HPLC) following the reflux extraction method as follows: 10 g of plant powder was weighed and refluxed with 70% methanol for 3 h at 45°C, the extract obtained was filtered through Whatman number 1 filter papers (Whatman ® qualitative filter paper, Grade 1, WHA1001325, Darmstadt, Germany) and the solvent removed in vacuo . After preparing the methanol extract 2.5 mg were dissolved in 1 mL of ACN for HPLC analysis (injection volume, 20 µL, flow rate, 1 mL/min, temperature, 22- 30°C, detection at 330 nm, and acetic acid was used to reduce the tailing).…”
Section: Methodsmentioning
confidence: 99%
“…1 and 2 were identified by analysing peaks at corresponding retention times by spiking with standards of the same corresponding compounds isolated and characterized earlier from I. cylindrica into methanol extract. 77 The amounts of 1 and 2 in the sample were quantified using standard spectrophotometric analytical methods (PerkinElmer's Lambda 35 UV/Vis, USA). The data were expressed as milligrams of chromones per gram of each fraction.…”
Section: Methodsmentioning
confidence: 99%
“…It showed the highest COX2 inhibition and potent free radical scavenging activity whilst also reducing inflammation better than stellatin and the NSAID indomethacin in a TPA induce mouse ear model. [80][81][82] Not only has this research identified a potential anti-inflammatory derivative which may have therapeutic value. It has begun to establish a structure activity relationship for COX2 inhibition.…”
Section: Developing Better Chemopreventive Agentsmentioning
confidence: 99%